2006
DOI: 10.1039/b514173g
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and NMR studies on GdIII, YIII, CuIIand ZnIIcomplexes of various DTPA–N,N″-bis(amide) ligands. Kinetic stabilities of the gadolinium(iii) complexes

Abstract: Three DTPA-derivative ligands, the non-substituted DTPA-bis(amide) (L(0)), the mono-substituted DTPA-bis(n-butylamide) (L(1)) and the di-substituted DTPA-bis[bis(n-butylamide)] (L(2)) were synthesized. The stability constants of their Gd3+ complexes (GdL) have been determined by pH-potentiometry with the use of EDTA or DTPA as competing ligands. The endogenous Cu2+ and Zn2+ ions form ML, MHL and M(2)L species. For the complexes CuL(0) and CuL(1) the dissociation of the amide hydrogens (CuLH(-1)) has also been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
(46 reference statements)
2
11
0
Order By: Relevance
“…This indicated that, when DTDTPA:Gd is grafted onto the Au nanoparticle, its transmetallation tends to be reduced. This behavior was also reported in a bisamide DTPA series for which the amide hydrogen atoms were gradually substituted with butyl groups, which induced a steric hindrance at the vicinity of the Gd center . The similar result obtained here suggested that the bulky nanoparticle rigidified the structure of the complex and prevented grafted DTDTPA:Gd complexes from extensive demetallation.…”
Section: Resultssupporting
confidence: 88%
“…This indicated that, when DTDTPA:Gd is grafted onto the Au nanoparticle, its transmetallation tends to be reduced. This behavior was also reported in a bisamide DTPA series for which the amide hydrogen atoms were gradually substituted with butyl groups, which induced a steric hindrance at the vicinity of the Gd center . The similar result obtained here suggested that the bulky nanoparticle rigidified the structure of the complex and prevented grafted DTDTPA:Gd complexes from extensive demetallation.…”
Section: Resultssupporting
confidence: 88%
“…In our polystyrene system, this surface-bound 64 Cu was easily removed by chromatography. The stability constants for DTPA or DOTA complexes with copper are similar, 21.5 and 22.25, respectively (25,41), but slightly higher for DOTA. It is possible for the polystyrene bead system that the large number of amine groups at the particle surface presented a competition binding site for the Cu 2+ ; if the metal was not preinserted into the chelator before conjugation to the nanoparticle surface, then the Cu 2+ bound to the surface of the nanoparticle rather than the DOTA and could be removed by chromatography.…”
Section: Discussionmentioning
confidence: 90%
“…dtpa amides are able to bind a variety of metal ions, ranging from lanthanides11,1318 and d elements19–22 to alkaline‐earth metals,23 pnictogens24 as well as elements of the boron group 19,24–32. Among this last group, Ga III is of particular interest due to its radioactive isotope 68 Ga, which is commonly used in positron emission tomography (PET).…”
Section: Introductionmentioning
confidence: 99%